2020
DOI: 10.1038/s41467-020-17558-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 1q21.2 and additional loci influence risk of spontaneous coronary artery dissection and myocardial infarction

Abstract: Spontaneous coronary artery dissection (SCAD) is a non-atherosclerotic cause of myocardial infarction (MI), typically in young women. We undertook a genome-wide association study of SCAD (N cases = 270/N controls = 5,263) and identified and replicated an association of rs12740679 at chromosome 1q21.2 (P discovery+replication = 2.19 × 10 −12 , OR = 1.8) influencing ADAMTSL4 expression. Meta-analysis of discovery and replication samples identified associations with P < 5 × 10 −8 at chromosome 6p24.1 in PHACTR1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 75 publications
(99 reference statements)
4
101
0
Order By: Relevance
“…In considering the role(s) of PHACTR1 in endothelial cells, the consequences of lower PHACTR1 or higher endothelin-1 in these cells could be additive or synergistic with effects in macrophages, as these two cell types play complementary and interactive roles in atherosclerosis(2). Moreover, the endothelial hypothesis may also have relevance to non-atherosclerotic vascular diseases associated with rs9349379-G, including migraine headache, arterial dissection, fibromuscular dysplasia, hypertension, and coronary microvascular dysfunction(28,60,61). Except for coronary microvascular dysfunction, the risk of these non-atherosclerotic vascular diseases is lower in carriers of the rs9349379-G variant in contrast to the higher risk of CAD conferred by rs9349379-G, indicating that future work is needed to link the polymorphism to these diseases.In summary, we present new roles for PHACTR1, MLC, and PP1 in efferocytosisand show that the PHACTR1 intronic rs9349379 CAD risk allele lowers the fully functional form of PHACTR1 protein and impairs efferocytosis in human atherosclerotic lesional macrophages and HMDMs.…”
mentioning
confidence: 99%
“…In considering the role(s) of PHACTR1 in endothelial cells, the consequences of lower PHACTR1 or higher endothelin-1 in these cells could be additive or synergistic with effects in macrophages, as these two cell types play complementary and interactive roles in atherosclerosis(2). Moreover, the endothelial hypothesis may also have relevance to non-atherosclerotic vascular diseases associated with rs9349379-G, including migraine headache, arterial dissection, fibromuscular dysplasia, hypertension, and coronary microvascular dysfunction(28,60,61). Except for coronary microvascular dysfunction, the risk of these non-atherosclerotic vascular diseases is lower in carriers of the rs9349379-G variant in contrast to the higher risk of CAD conferred by rs9349379-G, indicating that future work is needed to link the polymorphism to these diseases.In summary, we present new roles for PHACTR1, MLC, and PP1 in efferocytosisand show that the PHACTR1 intronic rs9349379 CAD risk allele lowers the fully functional form of PHACTR1 protein and impairs efferocytosis in human atherosclerotic lesional macrophages and HMDMs.…”
mentioning
confidence: 99%
“…Most of these loci were previously shown to be involved in multiple vascular diseases. LRP1 is a risk locus for pulse pressure 22 , migraine 23 , aortic abdominal aneurysm 24 , and was recently reported for spontaneous coronary artery dissection 25,26 involving the same risk allele for FMD that correlates with higher gene expression. However, the opposite allele was reported to increase the risk for MoyaMoya disease 27 and suggestively for CAD 28 .…”
Section: Discussionmentioning
confidence: 85%
“…The meta-analysis included participants of European ancestry from six studies: ARCADIA 8 /3C 47 GWAS, Mayo Vascular Disease Biorepository 48 , DEFINE-FMD study 42 , ARCADIA-POL 49 /WOBASZII 50 study, University of Michigan/Cleveland Clinic (UM) study 26,51 and FEIRI 7 /ASKLEPIOS 52 study. FMD patients presented similar clinical characteristics ( Supplementary Table S1 ) and homogeneous diagnosis, exclusion and inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In a genome wide association study (GWAS) comparing 5236 control subjects with 270 individuals suffering from spontaneous coronary artery dissection (SCAD), Saw and colleagues 53 described an association of rs12740679 at chromosome 1q21.2 with this pathology implicating the gene regulating the expression of the matrix protein A disintegrin and metalloproteinase with thrombospondin motifs-like protein 4 (ADAMTSL4) and lower expression levels of ADAMTSL4 with higher risk of SCAD. Furthermore, the authors also confirmed a respective association of SCAD with variants in the genes for phosphatase and actin regulator 1 (PHACTR1) on chromosome 6p24.1 and the low density lipoprotein receptor-related protein 1 (LRP1) gene at chromosome 12q13.3 as well as for the gene for multidrug resistance protein 6 (MRP6)/KCNE3 on chromosome 21q22.11.…”
Section: Big Data Smartphones and Other Wearable Devicesmentioning
confidence: 99%
“…The authors hypothesize that this inverse relationship and opposing genetic risk pattern for SCAD-associated myocardial infarction on the one hand and myocardial infarction caused by atherosclerosis of coronary arteries on the other hand points towards particular vascular genotypes impacting on the pathogenesis of different types of myocardial infarction. 53 …”
Section: Big Data Smartphones and Other Wearable Devicesmentioning
confidence: 99%